Mapeo de áreas abiertas ocupadas por bambúseas para la planificación y supervisión de intervenciones de limpieza = Mapping open bamboo areas for cleaning intervention planning and supervision - Hildt, Eduardo; Leszczuk, Andrés; Strieder, Diego; Alcalde, Julio (Facultad de Ciencias Forestales, Universidad Nacional de Misiones (UNaM) y EEA Montecarlo, INTA, 2024)
We evaluated the use of drone-based photogrammetry and digital cartography for supporting field activities in a native forest undergoing restoration. We captured images with a drone over an area of 34.4 hectares. Photogrammetric processing generated an orthomosaic and a 3D point cloud representing the terrain and canopy structure. Bamboo-dominated open areas were identified, totaling 7.57 hectares (22% of the total area). The collected data and the identified clearings were integrated into a geospatial PDF map. This map aided field personnel in targeted mechanical clearing of larger clearings while minimizing impact on the remaining forest.